Hyperoxia Leads to Transient Endocrine Alterations in the Neonatal Rat During Postnatal Development - Kowallick, Mirjam; Serdar, Meray; Markova, Boyka; Salveridou, Eva; Felderhoff-Müser, Ursula; Führer-Sakel, Dagmar; Heuer, Heike; Bendix, Ivo; Dewan, Monia Vanessa (Frontiers in Pediatrics, 2021)
Introduction: High oxygen concentrations have been identified as one factor contributing to the pathogenesis of preterm brain injury. The endocrine system plays an important role in neurodevelopment – especially the hypothalamus-pituitary-thyroid (HPT) axis, the hypothalamus-pituitary-adrenal (HPA) axis and the hypothalamus-pituitary-somatotropic (HPS) axis. Objective: The aim of this study was to investigate the effect of hyperoxia on the endocrine system in a rat model of hyperoxia-induced brain injury by analysing the activities of the HPT, HPA and HPS axes, respectively. Methods: Three-days old Wistar rats were exposed to hyperoxia (oxygen 80%, 48 hours). On postnatal day 5 (P5) and P11, transcript levels of thyroid-stimulating hormone (TSH), proopiomelanocortin and growth hormone (GH) were analysed in pituitary sections by in situ hybridization. Serologic quantification of TSH and thyroxine (T4), adrenocorticotropic hormone and GH were performed by Multiplex analysis and Enzyme-linked Immunosorbent Assay. Results: At P5, significantly lower GH levels were observed in pituitaries (mRNA) and in sera of rats exposed to hyperoxia. Serum TSH was significantly elevated without changes in T4. Conclusion: This is the first study demonstrating transient endocrine alterations in a rat model of hyperoxia-induced brain injury. The influence of these alterations on neurodevelopment needs to be determined.